Impact of postdiagnostic statin use on ovarian cancer mortality: A systematic review and meta‐analysis of observational studies - Li, Xia (Br J Clin Pharmacol, 2018)
AIMS: To comprehensively evaluate the association between postdiagnostic statin use and mortality of ovarian cancer (OC) patients. METHODS: Using a comprehensive strategy, multiple databases (Medline, Embase and Web of Science) were systematically searched to identify observational studies that examined the correlation between statin use and OC mortality up to 31 December 2017. The studies were independently reviewed and selected based on predetermined selection criteria. Data were extracted independently and in duplicate. The risk of bias was evaluated with the Newcastle–Ottawa scale. Hazard ratios (HRs) and 95% confidence intervals (CIs) for mortality were summarized with a profile likelihood random effects model. RESULTS: Of 269 studies, eight cohort studies of 19 904 OC patients met the inclusion criteria. Postdiagnostic statin use was inversely associated with all‐cause mortality/overall survival (summarized HR = 0.74; 95%CI = 0.63–0.87; I (2) = 55%; n = 7) and cancer‐specific mortality (summarized HR = 0.87; 95%CI = 0.80–0.95; I (2) = 0%; n = 3) of OC patients. These findings were consistent by subgroup analyses stratified by study and patient characteristics as well as adjustments made for potential confounders. A meta‐regression analysis found no effect of modification by these variables. Of note, similar significant inverse effects were also observed when increasing the intensity (highest vs. lowest) of postdiagnostic statin use (summarized HR = 0.84; 95%CI = 0.74–0.96; I (2) = 0%; n = 3). CONCLUSION: Postdiagnostic statin use can improve the survival of patients with OC. Further prospective cohort and randomized controlled trials are warranted to confirm the therapeutic role of statin use on the outcome of OC.